Analisis Yuridis Korban Salah Tangkap Ditinjau Dari Undang-Undang Nomor 8 Tahun 1981 Tentang Hukum Acara Pidana - Supiyati (Prodi Hukum S1 - Fakultas Hukum - Universitas Pamulang, 2024)
In a criminal case, there are investigation and investigative procedures carried out by the competent authorities in accordance with the oldest procedures in the provisions regulated in the Criminal Procedure Code (KUHAP). Arrests carried out by investigators are a form of special permission granted by law but this does not mean they can be carried out arbitrarily. Arrest is a very important legal process because it will affect the next stages of the legal process. Therefore, arrests must be carried out carefully, carefully and carefully by investigators. In Indonesia, several cases of victims of wrongful arrest often occur due to errors or negligence in the investigation and investigation process which are not in accordance with existing procedures or statutory regulations. This results in victims of wrongful arrest suffering both physically, psychologically and materially and receiving negative stigma from the public who knows about this. Mistakes in the arrest process have quite big consequences because if these mistakes are not immediately corrected they will continue in the following stages. If an error occurs in this process before the case is decided by the court, the suspect or his family can file a pre-trial hearing regarding the illegality of the arrest and can at the same time demand compensation.